從前瞻因應理論觀點探討翻轉教學策略應用 於退休準備課程在不同需求程度上之 教學成效 Exploring the Application of Flipped Teaching Strategies in Retirement Preparation Courses: An Analysis of Educational Effectiveness From the Perspective of Proactive Coping Theory Across Different Levels of Need - 胡夢鯨 Menq-Jing Hwu; 施宇澤 Yu-Ze Shih; 劉霽瑈 Ji-Rou Liu; 陳雅雯 Ya-Wen Chen (Journal of Research in Education Sciences, 2025)
隨著臺灣即將進入超高齡社會，如何讓屆退民眾預先做好退休準備、確保退休生活品質，是當前臺灣高齡社會一項重要課題。本研究目的在以退休前10年的公教人員為研究對象，透過翻轉教學實驗瞭解學習需求與實際學習效果的差距，再藉由退休準備教育課程需求現況調查，瞭解不同需求課程實施翻轉教學策略的成效，進而調整出適合屆退族群的退休課程與教學策略，以培養其充足的退休知識與應用能力，做好前瞻因應的退休準備。本研究採用問卷調查法進行需求調查，研究設計採分層隨機抽樣，研究工具「臺灣退休準備教育課程需求指標」以SurveyCake電子表單進行設計，共發出1,600份，回收有效樣本1,509份（94.31%）；然後應用準實驗研究法，進行翻轉教學成效的實驗，在實驗教學設計上，研究共招募50位學員，進行11週翻轉教學課程，每週一單元，每單元授課6小時，共41位實驗對象參與全程實驗課程，並完成「臺灣退休準備教育課程教學成效評估指標」之前測與後測。研究以Z分數、t檢定並配 合實驗效果量，建立退休準備教育課程不同需求層次，以及檢視翻轉教學實驗在知識提升與能力提升的成效，再透過交叉比對歸納出五種翻轉教學的後續進階實施方針。本研究結果發現，在46項退休準備教育課程需求指標中，高度需求有14項、低度需求有12項；而翻轉教學對於46項課程全部都能獲得在知識上與能力上的顯著提升。雖然可以證明翻轉教學實驗有助於退休準備教育的學習成效，但本研究更進一步檢視提升程度的效果量後，根據不同層面的教學實驗結果提岀五點建議：知識量大的課程應精簡學習內容、引導學習將知識轉成實際應用能力、調整課前及課後的指導活動、活化教學策略的活動，以及強化問題意識。本研究據此結果，提出對未來退休準備課程教學上的相關建議。 Research Background and Importance With advances in healthcare and public health policy, Taiwan’s population is aging rapidly, with a steadily increasing proportion of citizens aged 65 and above. Projections indicate Taiwan will enter a “super-aged society” by 2025, positioning it as one of the fastest-aging nations globally. This demographic shift underscores the urgency for retirement preparation education. Such education is integral to promoting quality of life for retirees over a projected 20-year post-retirement period. Research demonstrates that adequate retirement planning reduces anxiety, enhances independence, and increases life satisfaction, while insufficient planning often results in financial and lifestyle challenges. However, surveys show that Taiwanese residents generally fall short in retirement preparedness, with substantial gaps between retirement savings and ideal financial goals. Despite the established benefits of retirement education— such as improved mental and physical well-being, a more positive outlook on retirement, and reduced anxiety— there is no systematic retirement education program implemented on a national level in Taiwan. This study draws on proactive coping theory to address this gap by designing a core curriculum for retirement preparation education. The curriculum applies a flipped teaching strategy that promotes learner-centered engagement, combining principles from motivation theory, constructivism, and peer feedback to foster proactive engagement and practical application skills. Through needs assessments and experimental analysis, this research aims to develop a foundational framework to support Taiwan’s future retirement education initiatives.